Efavirenz-Based Regimens in Antiretroviral-Naive HIV-Infected Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. - Joanna Kryst; Paweł Kawalec; Andrzej Pilc (PLoS ONE)
Efavirenz, a non-nucleoside reverse-transcriptase inhibitor (NNRTI) is one of the most commonly prescribed antiretroviral drugs. The present article provides a systematic overview and meta-analysis of clinical trials comparing efavirenz and other active drugs currently recommended for treatment of HIV-infected, antiretroviral-naive patients. Electronic databases (Pubmed, Embase, the Cochrane Library, Trip Database) were searched up till 23 December 2013 for randomized controlled clinical trials published as a peer-reviewed papers, and concerning efavirenz-based regimens used as initial treatment for HIV infection. Thirty-four studies were included in the systematic review, while twenty-six trials were suitable for the meta-analysis. Efavirenz was compared with drugs from four different classes: NNRTIs other than efavirenz (nevirapine or rilpivirine), integrase strand transfer inhibitors (InSTIs), ritonavir-boosted protease inhibitors (bPI) and chemokine (C-C motif) receptor 5 (CCR5) antagonists (maraviroc), all of them were added to the background regimen. Results of the current meta-analysis showed that efavirenz-based regimens were equally effective as other recommended regimens based on NNRTI, ritonavir-boosted PI or CCR5 antagonist in terms of efficacy outcomes (disease progression and/or death, plasma viral HIV RNA <50 copies/ml) while statistically significant more patients treated with InSTI achieved plasma viral load <50 copies/ml at week 48. In comparison with both InSTI-based and CCR5-based therapy, efavirenz-based treatment was associated with a higher risk of therapy discontinuation due to adverse events. However, comparisons of efevirenz-based treatment with InSTI-based and CCR5-based therapy were based on a limited number of trials, therefore, conclusions from these two comparisons must be confirmed in further reliable randomized controlled studies. Results of our meta-analysis support the present clinical guidelines for antiretroviral-naive, HIV-infected patients, in which efavirenz is one of the most preferred regimens in the analyzed population. Beneficial safety profile of InSTI-based and CCR5-based therapy over efavirenz-based treatment needs further studies.